Типологические основания объяснения в сравнительно-историческом языкознании - Чекман, Валерий (Kalbotyra, 1983)
This article shows that every step of reconstruction is basically an explanation of some aspects of historical events, and the observational phenomena of languages (living and dead) are used as a corpus of explanatory facts. It is revealed that the reconstructed strata must have all the properties of language (the general principle of typological verisimilitude), and the results of reconstruction are to he verified typologically in every step (the particular principle of typological verisimilitude).